McDonaldization of Higher Education (Case Study: Thesis Jockey in Tanjungpinang City) - Habib Syahputra; Siti Arieta; Taufiqqurrachman Taufiqqurrachman (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
McDonaldization is a paradigm that occurs in modern society, shifting from formal rationality to an interest in practicality due to its perceived efficiency. In this context, McDonaldization in education promotes practical elements through the principles of McDonaldization, which are efficiency, predictability, quantification, and control (technology). This study aims to identify the McDonaldization of higher education through the behavior of thesis jockeys in the city of Tanjungpinang. The method used is a descriptive-qualitative approach that examines aspects of the McDonaldization of higher education in the behavior of thesis jockeys in Tanjungpinang, using the snowball technique with seven informants, including jockey service providers, student jockey service users, non-user students, and lecturers. The theoretical foundation used is Postmodern Theory (McDonaldization) by George Ritzer. The study results reveal that the efficiency aspect is the primary reason for Tanjungpinang city students to choose jockey services. In conclusion, the McDonaldization theory is applicable to higher education and influences the behavior of thesis jockeys in Tanjungpinang.